Effect of Injection Hole Diameter on Operational Conditions of Common-Rail Fuel-Injection System for Portinjection Hydrogen-Fueled Engine - Mohammed, Kamil; M. M., Rahman (Universiti Malaysia Pahang, 2015)
Modeling of the hydrogen-fueled engine injection system is a very important tool that can be used to explain or predict the effect of advanced injection strategies on combustion and emissions. This work proposes a common-rail (CR) injection system for a four-stroke four-cylinder hydrogen-fueled engine with a port-injection feeding system. A numerical one-dimensional gas dynamic model was developed considering a single injection event for each injector per cycle. For this purpose, one-dimensional flow equations in conservation form are used to simulate wave propagation phenomena throughout the CR (accumulator). The effect of the CR on the injection-system characteristics has been clarified. These characteristics include: rail pressure, sound velocity, rail mass flow rate, injected mass flow rate and pressure drop across injectors. The interaction effects of operational conditions (engine speed and rail pressure) and geometrical features (injector hole diameter) are illustrated. The required compromise solutions are highlighted. The CR injection system is shown to be a promising enhancement for the port-injection hydrogen-fueled engine.